The historical-hermeneutical prelude to the legacy of Karl Barth - Pelser, G. M. M. (HTS teologiese studies, 2007)
The article aims to explain Karl Barth’s hermeneutical legacy against the background of the influence of the Enlightenment in philosophy and theology during the nineteenth and twentieth centuries. It consists of a discussion of a “hermeneutic chart”, mapped by Schleiermacher, Dilthey, Bultmann, Ebeling, and Ricoeur. This “map” is introduced in the foreword by outlining mileposts and concluded by pointing to the so-called postmodern “hermeneutic critique against hermeneutics”. The cord that keeps the fragments of individuals’ contributions together in the article is the function of the notion “hermeneutic circle” and, especially, how this notion had been adapted since the Enlightenment through Romanticism until Dialectic Theology, conducing to present-day Postmodernity.